Hydrogeophysical exploration for estimating groundwater reservoirs areas in Southern Rhodes through ERT (Electrical Resistivity Tomography) method. - Karmis, P.; Giannoulopoulos, P.; Sofos, F.; Lappas, I. (Bulletin of the Geological Society of Greece, 2013)
The present study deals with the groundwater investigation of hydrogeological conditions of Southern Rhodes, in the search for additional groundwater supplies to support the water needs of the area. An extensive Hydrogeological – Geophysical research was conducted, aimed to identify exploitable groundwater zones. This geophysical survey was carried out along alluvial basins, looking for more permeable geological formations within the sequence of the Neogene and Quarternary deposits. The use of a high resolution geophysical method (ERT) was selected for targeting the shallow geological structures and hydrostratigraphy. Thirteen ERT sections of total length of approximately 34000m were measured, laid out primarily at the south eastern part of the island. The geophysical survey revealed that alluvial sediments have an average thickness of about 30m while nearby the coastal zone increase locally up to 50m. The hydrostratigraphical structure is characterized by three distinct sections, the overlying alluvial deposits, the intermediate clay-marls and the underlying coarse formations. Moreover, almost all fault zones which are reflected in the surface geological map are revealed in greater depths. Result of vertical tectonic movements is the uplift of geological formations with increased resistivity. Finally, the target areas were selected based on hydrogeological criteria and specifically taking into account the increased possibility of groundwater reservoirs within the alluvial aquifer.